Microhabitat nest cover effect on nest survival of the Red-Crested Cardinal - Segura, Luciano Noel (2012)
Predation is the primary cause of nest failure of birds and factors affecting predation risk have shaped the evolution of avian life histories. We evaluated the influence of microhabitat vegetation cover on Red-crested Cardinal (Paroaria coronata) nest survival in natural forests of central eastern Argentina. Using program MARK, we analyzed patterns of daily nest survival regarding variation of nest cover. In addition, we evaluated the effect of the date within the breeding season on nest survival. We found a cumulative probability of nest survival of 19% with daily nest survival rates increasing significantly with vegetation cover above the nest and decreasing linearly throughout the season. Increased cover most likely helped conceal and protect nests, and since vegetation above the nest had the highest impact, main predators are probably aerial. Also, decline in nest success with date might correspond to an increase in predator abundance and movement later in the breeding season. We suggest taking into consideration these patterns for future conservation and management of Red-crested Cardinal natural populations, as well as for studies in the evolution of avian life histories in tropical and south temperate species.